Online Dispute Resolution (ODR) as an Alternative to E-Commerce Dispute Settlement in Indonesia - Mutiara Nurpadila; Devis Siti Hamzah Marpaung (LEGAL BRIEF, 2021)
The internet is not only limited to being used as a medium of information that can be accessed into social media, but it also can be used to make valuable trade transactions that have been introduced in Indonesia, which is known as e-commerce. This allows disputes to occur in e-commerce transactions, usually occurring in a conventional relationship. Then if it becomes wider and there are many activities in trade and e-commerce transactions, there will be many disputes about e-commerce that must be resolved. However, by using online media, existing disputes can be resolved properly. If the use of communication and information technology is combined with Alternative Dispute Resolution (ADR). In this study, the researchers discussed how business settlement through Online Dispute Resosulion was implemented in Indonesia. It also provided an understanding of ODR and the law that used as an intermediary in resolving conflicts that occur in the community with internet media which were expected to mix in providing a good conflict resolution. This research was descriptive analytical. It was hoped that this research can be used as a new way of providing facilities to the Indonesian people for those who want to seek legal certainty and resolve disputes using ODR.